Pengaruh Rakitan Teknologi Produksi Terhadap Hasil, Kelayakan Usaha Penangkaran Benih dan Daya Tumbuh Benih Kedelai - Arifin, Zainal (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2018)
Implementation of soybean production technology of specific location with using high quality seeds of superior varieties is one of the important factors for achieving increased production of soybeans. This assessment was aimed to determine the effect of assembly seed production technology to yield, feasibility of seed breeding and viability. The experiment was conducted in lowland KP. Mojosari, Mojokerto regency which was held on dry season I 2013. Randomized experimental design with 6 replications in an area of 1.0 hectares was used in the experiment. The treatment consisted of five varieties, namely : (a) Anjasmoro, (b) Argomulyo, (c) Kaba, (d) Sinabung, and (e) Argomulyo (Farmer). Assessment of seed storage technology was conducted at Laboratory of Seed of AIAT East Java for 8. The result of study showed that the highest productivity was found in soybean medium seed type, namely Kaba varieties (2,41 t/ha of consumption seed and 1,96 t/ha labeled seed) and Sinabung (2,39 t/ha of consumption seed and 1,90 t/ha labeled seed) with each R/C value of 2,18 and 2,12 respectively, so that the seed breeding using the recommendation technology is economically feasible. The treatment of drying of large seed type (Anjasmoro and Argomulyo) and medium seed type (Kaba and Sinabung) had the viability > 80% with the retention period until the eighth month when the seeds are dried each 1 month with moisture content <10%. The cultivation technology and soybean storage Argomulyo way farmers without re-drying produce viability >80% which only occurs until the fourth month.